(3aQOhS GdMceIs - (3NGdO Hf jRjO Hf eYGhjg Hf CHj SajGf, CHh gGTe,J (B90 (3g` s
(3ChdgG (B:s
(3bGd CejQ NGdO Hf jRjO ai GdSHcjI heOMgG GdMeO ddg Ld Gddg ebJOQG eOHQkG gGOjkG aVdkG def TcQG s
(3BNQgG (B:s
(3aef HgPG GQGe GMLGQfG aGdMb ai GdJOHjQ MSHi eG HjfJ ef TGfgG hOhf eG jfSH GLRGg Je cJGH GdehShe HaQOhS GdMceI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B98s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1254s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs